Experiences of Support for Sexual Dysfunction in Men with Prostate Cancer: Findings from a U.K.-Wide Mixed Methods Study. Issue 3 (25th February 2021) - Watson, Eila; Wilding, Sarah; Matheson, Lauren; Brett, Jo; McCaughan, Eilis; Downing, Amy; Wright, Penny; Cross, William; Selby, Peter; Butcher, Hugh; Glaser, Adam; Gavin, Anna; et al.
ABSTRACT: Background: Men with prostate cancer (PCa) often experience sexual dysfunction following diagnosis and treatment, yet little is known about the support they receive to deal with this. Aim: To explore men's experiences of support for sexual dysfunction following PCa diagnosis. Methods: This study included a U.K.-wide survey of men 18–42 months post-diagnosis of PCa, identified through cancer registries. The survey measured sexual function and the extent to which men perceived sexual dysfunction to be a problem (Expanded Prostate Cancer Index Composite-26), access to and experience of medications, devices, and specialist services for sexual dysfunction, and included a free-text question for further comments. Analysis focussed on men who reported poor sexual function, which they considered a moderate or big problem. Descriptive statistics explored the characteristics of men offered intervention and those that found this helpful. Free-text responses were analyzed using thematic analysis. Outcome: The main outcome of this study was to assess access to and experience of medications, devices, and specialist services for sexual dysfunction. RESULTS: 39.0% of all survey respondents (13, 978/35, 823) reported poor sexual function, which they considered a moderate or big problem. 51.7% of these men were not offered any intervention to aid sexual functioning. 71.9% of those offered an intervention reported trying it, of whom 48.7% found the intervention helpful. Men treated with surgery or brachytherapy were most likely to be offered an intervention. Medication was the most commonly offered intervention and 39.3% of those who tried medication found this helpful. Although offered less often, approximately half of the men who tried devices or attended specialist services found the intervention helpful. Free-text responses indicated that barriers to accessing support included inadequate information and support from healthcare professionals, embarrassment, negative views about treatment options, concerns about side effects and safety, and inconsistencies between secondary and primary care. Barriers to continuing use included limited effectiveness of treatments, inadequate ongoing support, and funding constraints. Drivers of sexual recovery included patient proactivity and persistence with trying different treatment options and ongoing support from health professionals. Clinical Implications: There is an urgent need to ensure that all men are offered, and have equal access to, sexual care support, with referral to specialist services when required. Strengths & Limitations: This study presents data from a large, U.K.-wide, population-based study of men with PCa and includes quantitative and qualitative findings. The possibility of non-response bias should, however, be considered. CONCLUSION: There are significant shortcomings in the support offered to U.K. men with sexual dysfunction following diagnosis and treatment for PCa which need to be addressed.